The ENRICH Marital Satisfaction (EMS) Scale: a psychometric study in a sample of Portuguese parents - Nunes, Cristina (2022)
Marital satisfaction is a key construct in the assessment of a couple’s relationship, and it encompasses aspects such as the feelings of affection, trust, and companionship that arise from the exchanges between spouses. The ENRICH Marital Satisfaction (EMS) Scale has been widely used as a reliable measure to assess marital satisfaction. In the present study, we aimed to analyze the psychometric properties and the factor structure of the EMS Scale in a sample of Portuguese parents. A total of 205 mothers and fathers participated; 107 were women (52%), and 98 were men (48%), and the mean age was 38.39 years (SD = 5.85). The majority were two-parent families (89.3%), with children between the ages of 1 and 13 years (M = 6.90), 53% of whom were boys. The participants completed the EMS Scale together with the Parenting Stress Index Short Form and the Parenting Alliance Inventory. The results from a confirmatory factor analysis corroborate the two-dimensional structure of the instrument, with internal validity and reliability values that were suitable for application in the Portuguese population. The EMS Scale can be an important resource, with good psychometric quality, for professionals and researchers, which can be used in assessment and intervention programs, both at the individual and couple levels.